Distribution of phonation and pause durations in fluent speech and stutterers speech - KUNISZYK-JÓŹKOWIAK, W. (Archives of Acoustics, 2014)
This work is a fragment of investigations into an objective method of evaluation of speech fluency. The paper presents statistical distributions of phonation and pause durations in utterances of stutterers speaking with a simultaneous auditory feedback and synchronously with an echo and in utterances of fluently speaking subjects. It is shown that the speech envelope can be a source of information about both speech velocity and the degree of speech non-fluency. The most probable phonation and pause durations have been found to exist and a correlation between these durations and the duration of one syllable has been revealed. This make makes a speech velocity evaluation possible on the basis of statistical distributions of phonation and pause durations. Distributions of phonation and pause durations in fluent and non-fluent speech have been compared. Non-fluent speech contains shorter phonations than fluent speech. Total phonation durations have been determined in utterances of stutterers and fluently speaking subjects. They are much shorter in non-fluent utterances than in fluent ones. The total phonation distribution can be an important parameter in an evaluation of speech fluency.